Association Between Gut Microbiota and Autoimmune Thyroid Disease: A Systematic Review and Meta-Analysis - Gong, Boshen; Wang, Chuyuan; Meng, Fanrui; Wang, Haoyu; Song, Bo; Yang, Yang; Shan, Zhongyan (Frontiers in Endocrinology, 2021)
Background: Autoimmune thyroid disease (AITD) is characterized by thyroid dysfunction and deficits in the autoimmune system. Growing attention has been paid toward the field of gut microbiota over the last few decades. Several recent studies have found that gut microbiota composition in patients with AITD has altered, but no studies have conducted systematic reviews on the association between gut microbiota and ATID. Methods: We searched PubMed, Web of Science, Embase, and Cochrane databases without language restrictions and conducted a systematic review and meta-analysis of eight studies, including 196 patients with AITD. Results: The meta-analysis showed that the alpha diversity and abundance of certain gut microbiota were changed in patients with AITD compared to the controls. Chao1, the index of the microflora richness, was increased in the Hashimoto’s thyroiditis group compared to controls (SMD, 0.68, 95%CI: 0.16 to 1.20), while it was decreased in the Graves’ disease group (SMD, -0.87, 95%CI: -1.46 to -0.28). In addition, we found that some beneficial bacteria like Bifidobacterium and Lactobacillus were decreased in the AITD group, and harmful microbiota like Bacteroides fragilis was significantly increased compared with the controls. Furthermore, the percentage of relevant abundance of other commensal bacteria such as Bacteroidetes, Bacteroides, and Lachnospiraceae was increased compared with the controls. Conclusions: This meta-analysis indicates an association between AITD and alteration of microbiota composition at the family, genus, and species levels.